Anti-proliferative activities on HeLa cancer cell line of Thai medicinal plant recipes selected from MANOSROI II database - Jiradej Manosroi (2018)
Ethnopharmacological relevance: The Thai/Lanna medicinal plant recipe database MANOSROI II contained the medicinal plant recipes of all regions in Thailand for the treatment of various diseases including anti-cancer medicinal plant recipes. Aim of the study: To investigate anti-proliferative activity on HeLa cell lines of medicinal plant recipes selected from the Thai/Lanna medicinal plant recipe database MANOSROI II. Materials and methods: The forty aqueous extracts of Thai/Lanna medicinal plant recipes selected from the Thai/Lanna medicinal plant recipe database MANOSROI II were investigated for anti-proliferative activity on HeLa cell line by SRB assay. The apoptosis induction by caspase-3 activity and MMP-2 inhibition activity by zymography on HeLa cell line of the three selected aqueous extracts, which gave the highest anti-proliferative activity were determined. Phytochemicals and anti-oxidative activities including free radical scavenging activity, inhibition of lipid peroxidation and metal chelating inhibition activities were also investigated. Result: Sixty percentages of the medicinal plant recipes selected from MANOSROI II database showed anti-proliferative activity on HeLa cell line. The recipes of N031(Albizia chinensis (Osbeck) Merr, Cassia fistula L., and Dargea volubilis Benth.ex Hook. etc.), N039 (Nymphoides indica L., Peltophorum pterocarpum (DC.), and Polyalthia debilis Finet et Gagnep etc.) and N040 (Nymphoides indica L. Kuntze, Sida rhombifolia L., and Xylinbaria minutiflora Pierre. etc.) gave higher anti-proliferative activity than the standard anti-cancer drug, cisplatin of 1.25, 1.29 and 30.18 times, respectively. The positive relationship between the anti-proliferative activity and the MMP-2 inhibition activity and metal chelating inhibition activity was observed, but no relationship between the anti-proliferative activity and apoptosis induction, free radical scavenging activity and lipid peroxidation inhibition activity. Phytochemicals found in these extracts were alkaloids, flavonoids, tannins and xanthones, but not anthraquinones and carotenoids. The recipe N040 exhibited the highest anti-proliferative and MMP-2 inhibition on HeLa cancer cell line at 30 and threefolds of cisplatin, respectively (p<0.05), while recipe N031 gave the highest caspase-3 activity (1.29-folds over the control) (p<0.05). Conclusion: This study has demonstrated that recipe N040 selected from MANOSROI II database appeared to be a good candidate with high potential for the further development as an anti-cancer agent. © 2012 Published by Elsevier Ireland Ltd. All rights reserved.